Development of Disaster Mitigation E-Module Based on Physics Concepts - Anggraeni, Firdha Kusuma Ayu; Prihandono, Trapsilo (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to develop a disaster mitigation e-module based on physics concepts for students. The study used the 4D method for research and development but only covered development. The researcher analyzed the situation, students, concepts, tasks, and learning objectives during the definition stage. A questionnaire was given to validators and students for a limited trial. The product design stage involved gathering references, choosing media options, selecting images and videos for the e-module, and creating the e-module's cover content. In the third stage of development, researchers carried out validation and limited trials. The data obtained were analyzed descriptively. The experts in the field of materials and media conducted a comprehensive evaluation of the e-module, and their findings indicated that the module was of a high standard in all aspects. This e-module received positive feedback from the students based on the average response score obtained of 3.45. The score is categorized as very good. Therefore, creating an e-module on disaster preparedness using physics concepts is a feasible option for use in learning, especially related to contextual-based physics learning.